Factors Contributing to Bleeding in Breast Cancer Wounds: A Literature Review - Sari, Nurmila; Haryanto, Haryanto; Hastuti, Lidia (Faculty of Nursing, Universitas Hasanuddin, 2024)
Aims: In Indonesia, breast cancer ranks first in the number of new cases; there is a significant increase in the number of cases every year. Complications of breast cancer include bleeding that affects quality of life, psychology, activity limitations, anemia, increased treatment time, economic burden, and the threat of death. Breast cancer is often found in advanced stages, increasing the risk of bleeding. The literature review analyzes research articles that discuss factors associated with breast cancer wound bleeding. Methods: Inclusion criteria include articles discussing breast cancer bleeding, cancer in general, cancer wounds, themes relevant to research, research can be a quantitative, qualitative, mixed method, meta-analysis, in English and Indonesian, from 2013 to 2023, full text. Keywords in the database are